Robust neutralizing antibodies to SARS-CoV-2 infection persist for months - Wajnberg, Ania; Amanat, Fatima; Firpo, Adolfo; Altman, Deena R.; Bailey, Mark J.; Mansour, Mayce; McMahon, Meagan; Meade, Philip; Mendu, Damodara Rao; Muellers, Kimberly; Stadlbauer, Daniel; Stone, Kimberly; et al. (Science (American Association for the Advancement of Science), 2020)
As the number of daily COVID-19 cases continues to mount worldwide, the nature of the humoral immune response to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) remains uncertain. Wajnberg et al. used a cohort of more than 30,000 infected individuals with mild to moderate COVID-19 symptoms to determine the robustness and longevity of the anti–SARS-CoV-2 antibody response. They found that neutralizing antibody titers against the SARS-CoV-2 spike protein persisted for at least 5 months after infection. Although continued monitoring of this cohort will be needed to confirm the longevity and potency of this response, these preliminary results suggest that the chance of reinfection may be lower than is currently feared. Science , this issue p. 1227 Antibodies generated after mild to moderate SARS-CoV-2 infection are neutralizing and relatively stable for at least 5 months. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused a global pandemic with millions infected and more than 1 million fatalities. Questions regarding the robustness, functionality, and longevity of the antibody response to the virus remain unanswered. Here, on the basis of a dataset of 30,082 individuals screened at Mount Sinai Health System in New York City, we report that the vast majority of infected individuals with mild-to-moderate COVID-19 experience robust immunoglobulin G antibody responses against the viral spike protein. We also show that titers are relatively stable for at least a period of about 5 months and that anti-spike binding titers significantly correlate with neutralization of authentic SARS-CoV-2. Our data suggest that more than 90% of seroconverters make detectable neutralizing antibody responses. These titers remain relatively stable for several months after infection.